2015
DOI: 10.1186/s13054-015-0875-z
|View full text |Cite
|
Sign up to set email alerts
|

External validation of scores proposed for estimation of survival probability of patients with severe adult respiratory distress syndrome undergoing extracorporeal membrane oxygenation therapy: a retrospective study

Abstract: IntroductionThis study was designed as an external validation of the recently proposed Predicting Death for Severe ARDS on V-V ECMO (PRESERVE) score, The respiratory extracorporeal membrane oxygenation survival prediction (RESP) score and a scoring system developed for externally retrieved patients on extracorporeal membrane oxygenation (ECMO) at our institution. All scores are proposed for the estimation of survival probability after ECMO treatment for severe adult respiratory distress syndrome.MethodsData fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 22 publications
10
57
1
1
Order By: Relevance
“…Klinzing et al [53, 54] demonstrated that the PRESERVE and RESP scoring systems fail to predict mortality for patients receiving VA ECMO. The EuroSCORE was designed to predict the mortality of patients undergoing cardiac surgery and may correlate with the outcomes of postcardiotomy failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Klinzing et al [53, 54] demonstrated that the PRESERVE and RESP scoring systems fail to predict mortality for patients receiving VA ECMO. The EuroSCORE was designed to predict the mortality of patients undergoing cardiac surgery and may correlate with the outcomes of postcardiotomy failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients receiving ECMO had higher gilz expression than patients without ECMO. This rescue therapy is used in severe ARDS when conventional mechanical ventilation fails [5, 38]. As ECMO has been shown to have pro-inflammatory effects in vivo [39, 40], it is conceivable that GILZ induction was aimed at compensating for these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant research, ARDS management still consists mainly of supportive care, based on optimized ventilation and extracorporeal membrane oxygenation (ECMO) [5]. New therapeutic strategies based on modulation of inflammation, using mesenchymal stromal cells, miRNA, or regulatory T cells, have recently been proposed [68].…”
Section: Introductionmentioning
confidence: 99%
“…Acute Respiratory Distress Syndrome (ARDS) is still life threatening despite new strategies in mechanical ventilations [28,18,8]. Mortality and morbidity of chronic obstructive pulmonary disease (COPD) are also considerable [34,7].…”
Section: Introductionmentioning
confidence: 99%